4-Dodecylbenzenesulfonic acid (DBSA) promoted solvent-free diversity-oriented synthesis of primary carbamates, S-thiocarbamates and ureas1. Issue 93 (11th October 2015) - Sardarian, Ali Reza; Inaloo, Iman Dindarloo
<x xml:space="preserve">Abstract</x> A simple and efficient solvent-free preparation of primary carbamates, S-thiocarbamates and ureas from alcohols, phenols, thiols and amines in the presence of 4-dodecylbenzenesulfonic acid, as a cheap and green Brønsted acid, has been described.